PENGARUH PEMBERIAN KONSELING DENGAN TINGKAT KECEMASAN PADA PASIEN PEMASANGAN CHEMOPORT YANG MENJALANI KEMOTERAPI DI RUMAH SAKIT KOTA MEDAN - Silaen, Harsudianto (Universitas Prima Indonesia, 2019)
One of the side effects of chemotherapy using a needle that cancer patients undergo is inflammation of blood vessels. To reduce this effect you can use chemoport. For treatment, patients must control within the first week after chemoport installation until the wound is dry. Furthermore, you need to clean the device about 1.5 - 2 months.